A Study of Sexually Transmitted Infections Among Patients Attending Suraksha Clinic & Targeted Intervention Clinics In Nainital District: A Cross-Sectional Survey - Awasthi, Sadhana; Nagarkar, Ajay Kumar; Luthra, Gagandeep; Singh, Harpreet; Chaudhary, Kunal; Sharma, Rishi (Indian Journal of Community Health, 2024)
Background: Sexually transmitted infections (STIs) pose a global health threat, particularly among vulnerable populations. Aligned with the National AIDS Control Program, this study focuses on estimating the prevalence of STIs in India, targeting Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum, and Trichomonas vaginalis. The aim is to identify gaps, understand factors influencing STI screening, and propose improvements. Objectives: Uncover barriers in STI screening, diagnosis, and management at Suraksha and targeted intervention clinics. Identify socio-demographic factors associated with screening barriers. Methodology: Sample unit: Patients at Suraksha and TI clinics. Sample size: 577 participants, including community-surveyed and health camp attendees. Sampling design: Complete enumeration. Cross-sectional survey in specified Haldwani and Nainital clinics. Results: Age group 20-40 exhibits higher symptomatic individuals, underscoring the need for screening in young and middle-aged adults. Only 55% of positive cases sought treatment, citing stigma, mild symptoms, and unawareness. Health workers, especially spouses, play a crucial role in testing and counseling. Delayed presentation at health facilities due to long waiting times, mild symptoms, lack of awareness, and distance. Conclusions: While the program succeeds in various aspects, infrastructure improvement, heightened awareness, and addressing stigma are crucial. Recommendations include more staff, wider service publicity, and better availability of essential resources.